Detertminants of CO2 Emission Intensity: Manufacturing Firm-Level Evidence in Indonesia - Melisa Constantia (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2022)
The Indonesian economy has improved with the manufacturing sector as its primary growth driver. However, along with this development, the country inevitably faces environmental issues such as increased carbon emissions. Based on the firm-level dataset from the Indonesian large and medium manufacturing sector, this paper investigates the main factors related to the CO2 emission intensity of manufacturing firms. The emission carbon data is obtained by calculating the fuel consumption of plants converted into carbon dioxide emissions using emission factors. The result shows that the trend of carbon emission had increased, but the carbon emission intensity had improved. Performing panel data framework, this study uses OLS, 2SLS, and fixed effect model in analyzing the determinants of CO2 intensity. The result of the FE regression suggests that larger firms are emission efficient compared to small-sized firms. Similarly, capital- and labor-intensive firms are less carbon-intensive. Furthermore, firms that spend more on maintenance have emitted more, perhaps due to the adoption of high maintenance equipment by emission-intensive firms requiring more expenses.